Determination of the prevalence of hypertension and factors associated with blood pressure among hospitalised elderly in Hospital Serdang, Selangor, Malaysia - Hashidi, Siti Nurhaliza; Omar, Noraida; Adznam, Siti Nur ‘Asyura (Persatuan Pemakanan Malaysia, 2021)
Introduction: Increasing trends of hypertension has been recognised as a common disease among the elderly. This study aimed to determine the prevalence of hypertension and factors associated with blood pressure among hospitalised elderly. Methods: This was a cross-sectional study involving 124 patients in Hospital Serdang, Selangor, Malaysia. Data on socio-demography, medical background, anthropometry, blood biochemistry and lifestyle were collected through face-to-face interviews and medical records. Dietary intake was obtained through two days of food history. Malnutrition risks and stress level were determined using the Mini Nutritional Assessment Short-Form (MNA-SF) and the Geriatric Depression Scale (GDS). Results: There were 59.7% males and 40.3% females with mean age of 66.81±5.35 years. Majority were found to have hypertension (72.6%). Approximately 38.7% had normal body mass index (BMI). Most of them reported insufficient dietary intakes except for trans fats, sodium, and caffeine. Nearly 62.1% were engaged with physical activity, 23.4% were smoking, and 4.8% were taking alcohol. Approximately 66.1% and 86.3% were classified as having normal nutritional status and normal stress levels. In this study, the prevalence of hypertension among elderly patients warded in Hospital Serdang, Selangor was 72.6% and factors such as length of stay, number of co-morbidities, number of medications, having co-morbidities of hypertension, dyslipidaemia and diabetes mellitus, polypharmacy, height, BMI, fibre, polyunsaturated fat, dietary cholesterol, caffeine, and duration of physical activity were found to be associated with blood pressure. Conclusion: The present study found that majority of patients (72.6%) had hypertension. Future studies regarding factors associated with blood pressure are recommended.